Evaluating the complexity of engineered systems: A framework informed by a user case study. Issue 6 (7th September 2020) - Potts, Matthew W.; Johnson, Angus; Bullock, Seth
Abstract: Evaluating the complexity of an engineered system is challenging for any organization, even more so when operating in a System‐of‐Systems (SoS) context. Here, we analyze one particular decision support tool as an illustratory case study. This tool has been used for several years by Thales Group to evaluate system complexity across a variety of industrial engineering projects. The case study is informed by analysis of semistructured interviews with systems engineering experts within the Thales Group. This analysis reveals a number of positive and negative aspects of (i) the tool itself and (ii) the way in which the tool is embedded operationally within the wider organization. While the first set of issues may be solved by making improvements to the tool itself, informed by further comparative analysis and growing literature on complexity evaluation, the second "embedding challenge" is distinct, seemingly receiving less attention in the literature. In this paper, we focus on addressing this embedding challenge, by introducing a complexity evaluation framework, designed according to a set of principles derived from the case study analysis; namely that any effective complexity evaluation activity should feature collaborative effort toward building an evaluation informed by a shared understanding of contextually relevant complexity factors, iterative (re‐)evaluation over the course of a project, and progressive refinement of the complexity evaluation tools and processes themselves through linking project evaluations to project outcomes via a wider organizational learning cycle. The paper concludes by considering next steps including the challenge of assuring that such a framework is being implemented effectively.